THE EFFECT OF PENTAGON FRAUD ON POTENTIAL FRAUD IN FINANCIAL STATEMENTS IN STATE-OWNED ENTERPRISES LISTED ON THE STOCK EXCHANGE IN INDONESIA - Septian Dwi Putranto; Nur Sayidah (Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the factors that can detect the existence of fraud in financial statements. The focus of this research is to evaluate the impact of the pentagon fraud variables, namely pressure, opportunity, rationalization, competence, and arrogance, on financial statement fraud. The research object in this study was state-owned companies listed on the Indonesia Stock Exchange for the period of 2022 to 2024. The total sample in this study consisted of 19 companies, selected using the purposive sampling technique. Pressure was proxied by financial stability, financial targets, and external pressures, while competence was proxied by ineffective supervision. Rationalization was proxied by changes in auditors and audit opinions, competence was also proxied by changes in the board of directors, and arrogance was proxied by the frequency of CEO changes. The results of this study show that financial targets and changes in auditors have an impact on financial statement fraud, while financial stability, external pressures, ineffective supervision, audit opinions, changes in directors, and frequency of CEO changes have no effect on financial statement fraud.